A Pt3 cluster anchored on a C2N monolayer as an efficient catalyst for electrochemical reduction of nitrobenzene to aniline: a computational study. (3rd November 2021) - Wang, Shuang; Wang, Zhongxu; Shang, Yongchen; Tian, Yu; Cai, Qinghai; Li, Zhenxing; Zhao, Jingxiang
Abstract : A Pt3 cluster anchored on h-C2 N exhibits ultra-high catalytic activity towards nitrobenzene reduction with a small limiting potential (−0.19 V). Abstract : The electrochemical reduction of nitrobenzene to aniline (NBER) under ambient conditions is of great significance for sustainable industry and life. In this work, by means of density functional theory (DFT) computations, we have systematically investigated the potential of several (Pt n, n = 1–6 and 13) nanoclusters anchored on a holey C2 N monolayer (Pt n /C2 N) as NBER electrocatalysts. Our results revealed that Pt n /C2 N materials exhibit high stability due to the strong interaction between the Pt-5d orbital and the N-2p orbital in C2 N. Interestingly, among these Pt n /C2 N catalysts, Pt3 /C2 N is the most active catalyst for NBER because of its rather small limiting potential (−0.19 V), in which the hydrogenation of Ph–NO2 * to Ph–NOOH* is identified as the potential-determining step. Compared with other catalysts, the strongest binding strength of Ph–NOOH* on Pt3 /C2 N is responsible for its superior catalytic activity towards NBER. Our results provide a promising Pt cluster-based catalyst with high efficiency for NBER, which could open a new door for sustainable aniline production.